Synthesis of Schiff Bases, Oximes and Hydrazones of 1,2,4-Oxadiazole and 1,2,4-Triazoles - M. Awadallah, Adel (Asian Journal of Chemistry, 2010)
The synthesis of Schiff bases of aryl aldehydes with 4-aminooxadiazoline, 4-amino triazoles and 3-acetyl-1,2,4-triazole hydrazones is described. Oximes and hydrazones of differently substituted-3-acetyl-1,2,4-triazoles are also prepared in order to study their biological activity. The assignment of the structures of all synthesized compounds was based on spectral data (mass spectra, IR, 1H and 13C NMR).